Direct and simultaneous analysis of lipase-catalyzed hydrolysis of high-oleic oil model by chiral stationary phase HPLC-ELSD. (15th January 2022) - Choi, Yoonseok; Park, Jun-Young; Chang, Pahn-Shick
Graphical abstract: Highlights: Direct analytical method based on HPLC-ELSD with Chiralpak IA was developed. All oleoylglycerols including enantiomers and oleic acid were baseline-separated. Trioleoylglycerol hydrolysis by lipase from Pseudomonas fluorescens was measured. Whole isomeric composition of trioleoylglycerol hydrolysate can be determined. The method is simple, rapid, and precise to identify stereoselectivity of lipase. Abstract: A novel HPLC-based method for direct separation of trioleoylglycerol (TOG), a major component in high-oleic oils, and its seven hydrolysis products ( i.e., oleic acid, monooleoylglycerol (MOG) and dioleoylglycerol (DOG) isomers) was established using a chiral stationary phase column, Chiralpak IA. Within 20 min, all species including enantiomeric MOG (1- sn -MOG and 3- sn -MOG) and DOG (1, 2- sn -DOG and 2, 3- sn -DOG) were baseline-resolved with resolution factors over 1.5 between adjacent peaks. The established method was used for investigating the integral stereoselectivity, which is the selectivity concerning all hydrolysis steps, of lipase from Pseudomonas fluorescens (PFL) with TOG as substrate. The time-course of DOGs and MOGs indicated that PFL had selectivity for TOG hydrolysis in the order of sn -1, sn -2, and sn -3 position, while it preferred to hydrolyze 2, 3- sn -DOG over 1, 2- sn -DOG. Being rapid and accurate to evaluate integral stereoselectivity, this method could promote the development and application of lipases with target stereochemistry in the food industry.